An RPC-PET prototype with high spatial resolution - Blanco, A. (2004)
A small positron emission tomography system, based on the timing RPC technology has been built and tested. This first prototype is aimed at validating the expectations, derived from simulations, of a very high spatial resolution, which could be of value for the imaging of small animals. The system is composed of two counting heads, able to measure the photon interaction point in two dimensions, the transaxial dimension and the Depth of Interaction. Each head is composed of 16 independent stacked RPCs made from copper and glass (anode) electrodes. Point-like 22Na sources were so far reconstructed, using the standard filtered back-projection algorithm, with a spatial accuracy of 0.6 mm FWHM, free of parallax error.